Daya Antibakteri Ekstrak Etanol Bawang Sabrang (Eleutherine americana) terhadap Shigella dysentriae dan Salmonela enteritidis - Rizqy Dimas Monica; Achadiyani Achadiyani; Astrid F. Khairani; Michael V.L Tumbol (JURNAL ILMU KEFARMASIAN INDONESIA, 2020)
The bacteria Shigella dysentriae and Salmonella enteritidis are gram-negative bacteria in the family Enterobactericeae that cause gastroenteritis. Sabrang onion (Eleutherine americana) is a family Iridaceae, containing flavonoids, alkaloids and saponins. The aims of this study was to determine the antibacterial ablitiy and contact time of ethanol extracts sabrang onion on Shigella dysentriae and Salmonella enteritidis. Research methods of Laboratory experimental. The antibacterial ability of sabrang onions was measured by the agar diffusion modification method and contact time was measured based on the minimum kill concentration values ​​of Shigella dysentriae and Salmonella enteritidis. Research data analyzed with One way ANOVA. The results of ethanol extract of Sabrang onion have antibacterial ability against Shigella dysentriae and Salmonella enteritidis, there is a correlation between the concentration of Sabrang onion extract on inhibition zone diameter. The contact time for Shigella dysentriae showed ethanol extract of Sabrang on minimal kill concentration with an 8 hour contact time had a bactericidal effect with the result of a decrease in the number of bacteria 1000 times on the initial inoculum. The bactericidal effect on Salmonella enteritidis shows ethanol extract of Sabrang onions at a minimum kill concentration with contact time of 5 and 10 minutes. Ethanol extract of Sabrang onion has antibacterial ability against Shigella dysentriae and Salmonella enteritidis. There are differences in the antibacterial effects of ethanol extracts of Sabrang onions against Shigella dysentriae and Salmonella enteritidis at the same contact time with different minimum kill concentration.